2003
DOI: 10.1046/j.1365-2230.2003.01418.x
|View full text |Cite
|
Sign up to set email alerts
|

Pustular pyoderma gangrenosum

Abstract: Pyoderma gangrenosum (PG) is an idiopathic inflammatory disease of unknown aetiology, frequently associated with an underlying systemic condition such as inflammatory bowel disease or haematological malignancy. Its occurrence tends to parallel exacerbations of the underlying disease. Four clinical variants of PG have been described and these include ulcerative, pustular, bullous and vegetative types. We report two cases of the pustular form, which is an uncommon variant of PG, where the pustules do not progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…However, in one of the reports, two patients with quiescent inflammatory bowel disease developed pustular PG. [10] In our case series, two patients had a combination of pustular and ulcerative lesions in the absence of associated IBD. [2]…”
Section: Etiology and Pathogenesismentioning
confidence: 97%
See 1 more Smart Citation
“…However, in one of the reports, two patients with quiescent inflammatory bowel disease developed pustular PG. [10] In our case series, two patients had a combination of pustular and ulcerative lesions in the absence of associated IBD. [2]…”
Section: Etiology and Pathogenesismentioning
confidence: 97%
“…[22] It probably represents a localized, misdirected host-mediated effector cell response to cutaneous tissue antigenically changed by trauma in a patient with altered immune reactivity. [10] Pathergy is seen in nearly 25% of the patients with PG. [4] We have reported that pathergy is more common in PG associated with systemic disease.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…In more than half of cases, the disease is associated with extra-cutaneous diseases, such as inflammatory bowel disease, polyarthritis seronegative or seropositive, and hematologic malignancies. 4,5 Our patient had no underlying disease.…”
Section: Discussionmentioning
confidence: 75%
“…This type of PG is manifest as a more superficial ulceration, which is most frequent on the upper extremities, head or neck. The lesions begin as pustules that spread into plaques that may be studded with pustular lesions, particularly on the dorsum of the hands [8,9]. This variant has also been termed pustular vasculitis of the dorsal hands and neutrophilic dermatoses of the dorsum of the hands (FIGURE 6).…”
Section: Classification Of Pyoderma Gangrenosummentioning
confidence: 99%